Anaesthetic management of a patent ductus arteriosus (PDA) occlusion using an Amplatz canine duct occluder (ACDO) in a dog. Issue 1 (28th January 2020) - Binetti, Anna; Smets, Pascale; Bosmans, Tim; Schauvliege, Stijn
Abstract : Patent ductus arteriosus (PDA) is one of the most common diagnosed congenital disease in dogs that usually causes heart failure and death unless corrected at a young age. A 2.5‐year‐old female intact Coton de Tuléar was referred and diagnosed with a left to right shunt PDA. Closure of the PDA was performed via a minimally invasive approach by means of an Amplatz canine duct occluder device. In this case report, we describe a successful anaesthetic protocol that included premedication using a combination of acepromazine and methadone, induction with propofol and midazolam and maintenance with isoflurane in oxygen, as well as a lidocaine constant rate constant rate infusion for intraoperative analgesic and cardiovascular support. This protocol provided excellent intraoperative cardiopulmonary stability and a smooth and rapid recovery.